2022
DOI: 10.18844/cjes.v17i10.8252
|View full text |Cite
|
Sign up to set email alerts
|

Effective ways of teaching in distance education

Abstract: The purpose of this research is to obtain the opinions of primary school teachers about effective teaching methods in distance education. In this study, the phenomenology design, one of the qualitative research models, was used. The participant group of the research consists of 32 primary school teachers who gave education in various primary schools in the Astana, Kazakhstan, in the 2021–2022 academic year. Research data were collected with the semi-structured interview form developed by the researchers. Descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Namely, commercialization of technology is one of the main objectives of Kazakh research universities, along with educational and scientific activities. The analysis of best practices (Abdyrov et al, 2017;Shakirova et al, 2019) identified the following features of the world's most advanced research universities: high quality of human resources; continuous cooperation with employers and consumers in research and development; own modern research and experimental infrastructure, research facilities; independent management.…”
Section: Introductionmentioning
confidence: 99%
“…Namely, commercialization of technology is one of the main objectives of Kazakh research universities, along with educational and scientific activities. The analysis of best practices (Abdyrov et al, 2017;Shakirova et al, 2019) identified the following features of the world's most advanced research universities: high quality of human resources; continuous cooperation with employers and consumers in research and development; own modern research and experimental infrastructure, research facilities; independent management.…”
Section: Introductionmentioning
confidence: 99%